Exergetic cost evaluation of hydrogen production powered by combined flash-binary geothermal power plant. (26th October 2015) - Yilmaz, Ceyhun; Kanoglu, Mehmet; Abusoglu, Aysegul
Abstract: A combined flash-binary geothermal plant and a water electrolysis unit for hydrogen production are considered and thermodynamic and exergoeconomic analyses of the system are performed. A liquid geothermal water resource at 200 °C with a flow rate of 100 kg/s is considered. The power produced in the plant is used for the electrolysis process. The electrolysis water can be preheated to 70 °C by the geothermal water leaving the power plant and hydrogen can be produced at a rate of 0.0498 kg/s. The exergy efficiency of the power plant and the overall system are calculated to be 46.6% and 45.8%, respectively. The unit exergetic cost of electricity from the power plant is 11.1 $/GJ (or 0.0400 $/kWh) and that of the produced hydrogen is 26.1 $/GJ (or 3.14 $/kg H2 ). Highlights: A combined flash-binary geothermal plant and a water electrolyzer for hydrogen production are considered. Exergetic cost analysis of the system is performed. The unit exergetic cost of electricity from the power plant is 11.1 $/GJ (or 0.0400 $/kWh). The unit exergetic cost of hydrogen is 26.1 $/GJ (or 3.14 $/kg H2 ).